2015
DOI: 10.1371/journal.pone.0122972
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Recognition and Modification by the Nosiheptide Resistance Methyltransferase

Abstract: BackgroundThe proliferation of antibiotic resistant pathogens is an increasing threat to the general public. Resistance may be conferred by a number of mechanisms including covalent or mutational modification of the antibiotic binding site, covalent modification of the drug, or the over-expression of efflux pumps. The nosiheptide resistance methyltransferase (NHR) confers resistance to the thiazole antibiotic nosiheptide in the nosiheptide producer organism Streptomyces actuosus through 2ʹO-methylation of 23S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Here, the Tsr dimer was confirmed to bind two SAM molecules in vitro, but shown to exhibit Michaelis–Menten kinetics for SAM turnover, which suggests that a single catalytic SAM binding site operates independently of a non‐catalytic binding site when both are occupied with SAM. This coincides with the recent findings by Yin and co‐workers that showed catalytic activity for an Nhr heterodimer containing a functionally inactivated subunit[40]. However, it could not be determined whether this functional difference in Tsr is structurally predefined.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Here, the Tsr dimer was confirmed to bind two SAM molecules in vitro, but shown to exhibit Michaelis–Menten kinetics for SAM turnover, which suggests that a single catalytic SAM binding site operates independently of a non‐catalytic binding site when both are occupied with SAM. This coincides with the recent findings by Yin and co‐workers that showed catalytic activity for an Nhr heterodimer containing a functionally inactivated subunit[40]. However, it could not be determined whether this functional difference in Tsr is structurally predefined.…”
Section: Discussionsupporting
confidence: 88%
“…The apo‐structure for Tsr has not been reported, but apo ‐ and SAM‐bound structures of Nhr are largely similar[12], implying that the catalytic site is fixed and inherently defined. As well, although SAM binding by the Nhr heterodimer was not evaluated[40], our present findings predict that SAM would distinguish between two potential binding sites on the Nhr heterodimer and accordingly, catalysis would proceed from a structurally pre‐defined catalytic site. Such structure‐defined functional asymmetry in a homodimeric enzyme is exemplified by the E. coli glyoxalase I, where only one of the enzyme subunits is able to bind metal and function catalytically[41].…”
Section: Discussionmentioning
confidence: 67%
“…In contrast, thiopeptides with 26-membered macrocycles (e.g., thiostrepton, siomycin, nosiheptide, berninamycin, and thiocillin/micrococcin) target the 50S subunit of by interacting with the 23S rRNA and ribosomal protein L11. ,, Binding is mediated primarily by interaction with 23S rRNA and is cooperative with L11. Resistance to thiopeptides of this variety occurs through mutation of either 23S rRNA or L11. , Alternatively, methylation of the 23S rRNA also confers resistance. Improving initial models, , more recent structural studies based on NMR, X-ray crystallography, and molecular modeling showed that these 26-membered thiopeptides bind to a cleft between the 23S rRNA and L11, , but covalent capture data suggest binding may be more on the surface of the rRNA and not between 23S/L11 . The interface of the 23S rRNA and L11 is called the “GTPase-associated center” and is crucial for ribosome function given its interaction with many translation factors. Consequently, the binding of thiopeptides with a 26-member macrocycle in this area can affect all phases of translation, but the most studied effects are on EF-Tu and EF-G during elongation. Inhibition of EF-Tu and tRNA delivery presumab...…”
Section: Thiopeptidesmentioning
confidence: 99%
“…This enhanced substrate preference for the 29-nucleotide hairpin is most likely due to increased accessibility of the target nucleotide in the hairpin which lacks the complex tertiary structure of the full 58-nt rRNA domain. The nosiheptide-resistance methyltransferase (NshR), a close relative of TsnR, methylates the same site on the 23S rRNA and also displays similar specificities for a 29-nucleotide fragment (77). Interestingly, both TsnR and NshR make a critical contact with nucleotide U1061, located in an internal loop within Helix 43 more distant from the target site, that allows for efficient substrate binding (76).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%